Impact of tobacco control policies on smoking-related cancer incidence in Germany 2020 to 2050: a simulation study - Gredner, Thomas; Niedermaier, Tobias; Brenner, Hermann; Mons, Ute (Cancer epidemiology, biomarkers & prevention, 2020)
Background: Germany is known for its weak tobacco control. We aimed to provide projections of potentially avoidable cancer cases under different tobacco control policy intervention scenarios. - Methods: To estimate numbers and proportions of potentially avoidable cancer cases under different policy intervention scenarios (cigarette price increases, comprehensive marketing ban, and plain packaging), we calculated cancer site-specific potential impact fractions by age, sex, and year of study period (2020-2050), considering latency periods between reduction in smoking prevalence and manifestation in declining cancer excess risks. To obtain estimates of future incident case numbers, we assumed a continuation of recent smoking trends, and combined German cancer registry data with forecasted population sizes, published effect sizes, and national daily smoking prevalence data. - Results: Over a 30-year horizon, an estimated 13.3% (men 14.0% and women 12.2%) of smoking-related cancer cases could be prevented if a combination of different tobacco control policies were to be implemented in Germany, with repeated price increases being the most effective single policy (men 8.5% and women 7.3%). Extensive sensitivity analyses indicated that the model is fairly robust. - Conclusions: Our results suggest that the expected cancer incidence in Germany could be considerably reduced by implementing tobacco control policies as part of a primary cancer prevention strategy. - Impact: Our straightforward modeling framework enables a comparison of the impact of different health policy measures. To further accelerate the currently observed tentative trend of declining smoking prevalence in Germany and thereby curtail smoking-related cancer incidence, there is a great need to urgently intensify efforts in tobacco control.